Novel Genetic Determinants of Dental Maturation in Children. (March 2023) - Grgic, O.; Prijatelj, V.; Dudakovic, A.; Vucic, S.; Dhamo, B.; Trajanoska, K.; Monnereau, C.; Zrimsek, M.; Gautvik, K.M.; Reppe, S.; Shimizu, E.; Haworth, S.; et al.
Dental occlusion requires harmonious development of teeth, jaws, and other elements of the craniofacial complex, which are regulated by environmental and genetic factors. We performed the first genome-wide association study (GWAS) on dental development (DD) using the Demirjian radiographic method. Radiographic assessments from participants of the Generation R Study (primary study population, N 1  = 2, 793; mean age of 9.8 y) were correlated with ~30 million genetic variants while adjusting for age, sex, and genomic principal components (proxy for population stratification). Variants associated with DD at genome-wide significant level ( P  < 5 × 10 −8 ) mapped to 16q12.2 ( IRX5 ) (lead variant rs3922616, B  = 0.16; P  = 2.2 × 10 −8 ). We used Fisher's combined probability tests weighted by sample size to perform a meta-analysis ( N  = 14, 805) combining radiographic DD at a mean age of 9.8 y from Generation R with data from a previous GWAS ( N 2  = 12, 012) on number of teeth (NT) in infants used as proxy of DD at a mean age of 9.8 y (including the ALSPAC and NFBC1966). This GWAS meta-analysis revealed 3 novel loci mapping to 7p15.3 ( IGF2BP3: P  = 3.2 × 10 −8 ), 14q13.3 ( PAX9: P  = 1.9 × 10 −8 ), and 16q12.2 ( IRX5: P  = 1.2 × 10 −9 ) and validated 8 previously reported NT loci. A polygenic allele score constructed from these 11 loci was associated with radiographic DD in an independent Generation R set of children ( N  = 703; B  = 0.05, P  = 0.004). Furthermore, profiling of the identified genes across an atlas of murine and human stem cells observed expression in the cells involved in the formation of bone and/or dental tissues (>0.3 frequency per kilobase of transcript per million mapped reads), likely reflecting functional specialization. Our findings provide biological insight into the polygenic architecture of the pediatric dental maturation process.